1995
DOI: 10.1159/000292405
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adhesion Formation following Ovarian Reconstruction with Fibrin Glue in the Rabbit

Abstract: To compare postoperative adhesion formation following ovarian reconstruc tion with fibrin glue or the microsurgical suturing technique, an experimental study was performed on sixteen adult female rabbits. While left ovaries were reapproximated with 6-0 coated polyglactin using a microsurgical technique, right ovaries were reconstructed with fibrin glue following ovarian bisection. Four weeks later, second-look laparotomies were performed to evaluate the adnexal adhesions. These were scored according to the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Animal or human studies have used autologous fibrin, 20 cryoprecipitate, 12,16 or commercial fibrin sealants such as Beriplast™ 19,22,26 or Tisseel (or its equivalents, TissuCol™, Hemaseel™), which contain a fibrinolysis inhibitor (aprotinin). 11,[13][14][15]17,18 The effectiveness of the fibrin preparation may be partly related to its persistence on tissue, which in turn is related to its ability to resist degradation by plasmin. Some commercial products contain aprotinin, a protein derived from bovine lung.…”
Section: Introductionmentioning
confidence: 99%
“…Animal or human studies have used autologous fibrin, 20 cryoprecipitate, 12,16 or commercial fibrin sealants such as Beriplast™ 19,22,26 or Tisseel (or its equivalents, TissuCol™, Hemaseel™), which contain a fibrinolysis inhibitor (aprotinin). 11,[13][14][15]17,18 The effectiveness of the fibrin preparation may be partly related to its persistence on tissue, which in turn is related to its ability to resist degradation by plasmin. Some commercial products contain aprotinin, a protein derived from bovine lung.…”
Section: Introductionmentioning
confidence: 99%
“…In the rabbit model, De Iaco et al [10] demonstrated that postoperative adhesion scores in animals after laparoscopic fibrin sealant application on uterine horn lesions are significantly lower compared to control animals. Bilgin et al [11] recently demonstrated in the rabbit model that ovarian reconstruction with fibrin glue does not reduce postoperative adhesion forma tion when compared with microsurgical suturing. How ever, as underlined by the authors, studies comparing fibrin glue reconstruction with leaving the ovary open are needed [11].…”
Section: Discussionmentioning
confidence: 99%
“…Bilgin et al [11] recently demonstrated in the rabbit model that ovarian reconstruction with fibrin glue does not reduce postoperative adhesion forma tion when compared with microsurgical suturing. How ever, as underlined by the authors, studies comparing fibrin glue reconstruction with leaving the ovary open are needed [11]. In the present study we found no difference in periovarian and periuterine adhesion formation be tween the fibrin sealant-covered side and the control uncovered, unsutured side in a model in which each ani mal served as its own control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations